2007
DOI: 10.5465/amj.2007.26279222
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Predictors of Women on Corporate Boards

Abstract: Women are increasing in number among corporations' boards of directors, yet their representation is far from uniform across firms. In this study, we adopted a resource dependence theory lens to identify organizational predictors of women on boards. We tested our hypotheses using panel data from the 1,000 U.S. firms that were largest in terms of sales between 1990 and 2003. We found that organizational size, industry type, firm diversification strategy, and network effects (linkages to other boards with women d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

46
898
5
17

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,015 publications
(966 citation statements)
references
References 81 publications
(85 reference statements)
46
898
5
17
Order By: Relevance
“…Figure 1 illustrates the interaction effects based on state of the art plotting procedures (Aiken and West 1991;Tang et al 2011). These results support the hypothesis that director embeddedness reduces gender discrimination through unequal executive compensation and can be used as further indication that embedded directors might use the multitude of board seats as a learning platform (Shropshire 2010;Hillman et al 2007;Haunschild and Beckman 1998). The experience that directors gain via their network embeddedness might affect their assessment of language barriers and proposed transaction costs in a positive way and reduce the compensation discount that is passed on to female managers.…”
Section: Gender Pay Gapsupporting
confidence: 64%
See 2 more Smart Citations
“…Figure 1 illustrates the interaction effects based on state of the art plotting procedures (Aiken and West 1991;Tang et al 2011). These results support the hypothesis that director embeddedness reduces gender discrimination through unequal executive compensation and can be used as further indication that embedded directors might use the multitude of board seats as a learning platform (Shropshire 2010;Hillman et al 2007;Haunschild and Beckman 1998). The experience that directors gain via their network embeddedness might affect their assessment of language barriers and proposed transaction costs in a positive way and reduce the compensation discount that is passed on to female managers.…”
Section: Gender Pay Gapsupporting
confidence: 64%
“…Networks lead to the formation of elites (Davis and Greve 1997;Useem 1982). With respect to gender, these elites are predominately male (Daily et al 1999;Bilimoria andPiderit 1994, Brammer et al 2009;Adams and Ferreira 2009;Huse et al 2009;Hillman et al 2007). Among groups with similar demographical attributes, homophilous behavior can be observed (McPherson and Smith-Lovin 1987).…”
Section: Network Embeddedness Effects On Discriminationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this manner, networks create a shared social environment (Weick & Roberts, 1993) where organizations convey the value of certain practices to others in the network (Hillman, Shropshire, & Cannella, 2007) regardless of whether or not the practices enhance or diminish social or environmental welfare (Kang, 2008;Pfarrer, Smith, Bartol, Khanin, & Zhang, 2008).…”
Section: Structural Elements: Board Networkmentioning
confidence: 99%
“…For instance, a group of researchers found that gender plays an imperative role in determining level of firm performance [17][18][19]. In contrast, past studies such as reported by a researcher showed insignificant role of gender in predicting firm performance [20][21][22]. In the perspective of the effects of independent directors, these independent directors were deemed to be able to provide greater integrity and offer impartial judgment in the agency theory, while the resource dependency theory considers the role of external resources in affecting firm behaviors [23,24].…”
Section: Introductionmentioning
confidence: 99%